The Effect of Character-Based Learning Media Integrated with Local Wisdom in Enhancing Elementary Students' Literacy Skills and Character Development - Lestari, Luh Putu Sri; Septiari, Ni Kadek; Kristiantari, MG. Rini; Listyana, I Gusti Agung Ayu Putu (Yayasan Keluarga Guru Mandiri, 2026)
Developing students' literacy skills and character values is essential in fostering holistic competencies in elementary education. However, conventional learning media often lack contextual relevance and fail to integrate cultural values, limiting their impact on students' personal and academic development. This study investigates the effect of character-based learning media integrated with local wisdom on students' literacy skills and character development. A quasi-experimental research design was applied, involving elementary school students assigned to experimental and control groups. The data were gathered through literacy performance assessments and character observation rubrics. Multivariate analysis of variance (MANOVA) was employed to analyze the effectiveness of the intervention. The results showed that students who engaged with character-based media grounded in local wisdom demonstrated significantly greater improvement in both literacy proficiency and character traits compared to the control group. The integration of culturally relevant content with character education principles allowed students to connect more deeply with learning materials and internalize core values such as responsibility, respect, and cooperation. These findings highlight the potential of localized, value-driven learning media in enhancing not only academic achievement but also moral and social development. The study suggests that adopting culturally rooted and character-based pedagogical approaches can substantially enrich elementary education practices.